1997
DOI: 10.1038/sj.sc.3100430
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of spinal cord injuries that occur in swimming pools

Abstract: The purpose of this study was to determine the usual circumstances surrounding spinal cord injuries that occur in swimming pools so that appropriate primary prevention programs targeted at high risk persons, activities, and environments could be developed and initiated. A sample of 341 persons enrolled in the National Spinal Cord Injury Statistical Center database since 1973 whose injury was the result of a swimming pool mishap was identi®ed. Medical records were reviewed retrospectively and a survey questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 26 publications
2
59
2
3
Order By: Relevance
“…In this series, diving accidents comprised 2.5% of all cervical spine trauma admitted to the department. Most patients were male (97%) with a mean age of 27 years; this is in accordance with others series [1,4,6,8]. It is likely that the number of cervical injuries seen in this study is probably underestimated, because minor injuries were not admitted to the department, but seen only in emergency departments or by general practitioners.…”
Section: Circumstances Of Cervical Traumasupporting
confidence: 74%
See 2 more Smart Citations
“…In this series, diving accidents comprised 2.5% of all cervical spine trauma admitted to the department. Most patients were male (97%) with a mean age of 27 years; this is in accordance with others series [1,4,6,8]. It is likely that the number of cervical injuries seen in this study is probably underestimated, because minor injuries were not admitted to the department, but seen only in emergency departments or by general practitioners.…”
Section: Circumstances Of Cervical Traumasupporting
confidence: 74%
“…These injuries cause substantial mortality and morbidity, with many patients acquiring a significant and permanent disability [1,4,8,9,15]. According to different series, the incidence of diving accidents represents from 1.2 to 22% of all spinal cord injuries [1,3,11,12,20].…”
Section: Circumstances Of Cervical Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that of the SCIs resulting from diving headfirst into a swimming pool, 75% occurred in a pool with no depth indicator. 25 Ninety-five percent of people receiving an SCI from a swimming incident dove into water less than 8 ft deep. 25 A primary prevention technique for these injuries is to clearly mark the depth around swimming pools.…”
Section: Firearm-related Injuriesmentioning
confidence: 99%
“…25 Ninety-five percent of people receiving an SCI from a swimming incident dove into water less than 8 ft deep. 25 A primary prevention technique for these injuries is to clearly mark the depth around swimming pools. Depth indicators can be purchased from a pool supply store.…”
Section: Firearm-related Injuriesmentioning
confidence: 99%